1993
DOI: 10.1007/bf00029875
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in South Korean natural populations of wild soybean (Glycine soja)

Abstract: Wild relatives are valuable genetic resources for crop improvement . Evaluating genetic variation in these species is not only important for their use in breeding programs, but will also provide information about evolution of crops . Seeds representing six natural populations were used to study the level of variation in the South Korean wild soybean . Electrophoretic assays of the seeds on horizontal slab gels were conducted to determine the genotypes of each natural plant at 35 loci in 17 isozymes and one pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
26
1
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 23 publications
4
26
1
1
Order By: Relevance
“…Japanese accessions showed high genetic relationship to Korean soybean gene pools, whereas Southeast Asian accessions were similar to Chinese accessions. As previous studies (Lee et al, 2011;Lee et al, 2008;Li & Nelson, 2001;Yu & Kiang, 1993), soybean germplasm of Korea region conserve distinct genetic diversity compared to Chinese accessions, and Japanese and Korean accessions were more similar to each other. By model-based bayesian clustering method showed that Korean soybean accessions could be subdivided into five subpopulation (Pop-2~Pop6).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Japanese accessions showed high genetic relationship to Korean soybean gene pools, whereas Southeast Asian accessions were similar to Chinese accessions. As previous studies (Lee et al, 2011;Lee et al, 2008;Li & Nelson, 2001;Yu & Kiang, 1993), soybean germplasm of Korea region conserve distinct genetic diversity compared to Chinese accessions, and Japanese and Korean accessions were more similar to each other. By model-based bayesian clustering method showed that Korean soybean accessions could be subdivided into five subpopulation (Pop-2~Pop6).…”
Section: Discussionsupporting
confidence: 57%
“…Recently, the usage of soybean for biodiesel has made this crop more economically important, and the whole-genome sequencing of Williams 82 (G. max) and IT182932 (G. soja) have been completed accordingly (Hisano et al, 2007;Kim et al, 2010;Schmutz et al, 2010). Yu & Kiang (1993) reported that Korea might be one of the major center of soybean origins based on electrophoretic assays of wild soybean (G. soja) and cultivated soybeans (G. max). Lee et al (2008) also suggested that Korea is a major center of diversity for wild soybean and potentially could serve useful alleles not found in other parts of the world while Dong et al (2004) regarded northeastern region of China as major center of soybean origin.…”
mentioning
confidence: 99%
“…The biological diversity in both cultivated and annual wild soybeans has been investigated by phenotypic analysis (Dong et al 2001, as well as by using various molecular markers like isozymes, RFLP, SSR (Keim et al 1992;Yu and Kiang 1993;Skorupska et al 1993;Dong et al 2001Dong et al , 2004Abe et al 2003;Kuroda et al 2006;. As expected for a large and complex genome of polyploid origin Walling et al 2006), the soybean genome is heavily methylated by 5-methyl-cytosines, predominantly at repetitive sequences located in the heterochromatic centromeric regions (Zhu et al 1994;Young et al 1999).…”
mentioning
confidence: 99%
“…Some researchers identified the distribution of the genetic diversity of G. soja in Korea. Yu and Kiang (1993) examined 35 loci in 17 isozymes and trypsin inhibitors and reported a surprisingly high variation, suggesting that Korea is likely to be one of the major soybean gene centers. An analysis of genetic variation using RAPD and isozyme techniques also indicated that overall genetic variation among the wild soybeans was greater than that of the cultivated soybeans.…”
Section: Introductionmentioning
confidence: 99%